Studying the Effect of the Technological Factor in Raising the Degree of Architectural life in Residential Buildings as a Complementary Factor to Salingaros’ Equations - ودح هاني; سعيد نسيبة; حسين هلا (Latakia University Journal -Engineering Sciences Series, 2022)
In light of the modern trends of architecture and the multiplicity of methods and ideas put forward by many thinkers and theorists, We notice that architecture has begun to lose its humanity and turn into a consumer item that negatively affects architectural life, culture, and society. It was necessary to invest in modern architectural theories and proposals, which aim to design an effective architectural environment that supports human life. In addition, technology has become an urgent and necessary need to keep pace with the tremendous and rapid development in the requirements of modern architecture, using modern technologies that provide comfort (psychological and physical) for the inhabitant. How can we achieve a kind of integration between an architecture full of humanity and life, and an architecture that adopts technology to raise the standard of life in residential buildings? The researcher relied on measuring the degree of life in residential spaces using Salingaro’s equations, with the addition of a new factor, the technological factor, so that we can achieve integration between the technological and architectural factors to improve the degree of life in the dwelling. The research reached an important conclusion, which is that the technological factor has a positive and effective role in raising the degree of life in residential spaces, and its effect is not constant, but rather decreases with the passage of time.